(untitled) (Jurnal Pustaka, 2026)
Land certificates are proof of ownership of a plot of land that serves as a means of proving the truth of data physically and legally on the land, so that land owners obtain legal certainty and legal protection from overlapping that results in losses experienced by one of the parties in the problem. The purpose of this study was to determine legal certainty and legal protection and the steps that will be taken to resolve problems with certificates that experience overlapping. The research method used in this study is a qualitative method as a method that focuses on a deep understanding of a problem that occurs, so that in this study using interviews, observations and document analysis as a form of data collection methods carried out in obtaining information on overlapping that occurs. Based on the results of a case study conducted at the Sawahlunto City Land Office, there are steps taken in order to provide legal certainty through land registration as a form of preventing overlapping from occurring and there are preventions carried out both internally and externally in avoiding overlapping.